Titanium-based super battery capacitor and preparation method thereof

By using lithium titanate/carbon composite materials and lithium nickel cobalt manganese oxide and other materials, the particle size and weight ratio of the battery module are optimized, and the high porosity separator is combined with a high porosity separator, the problems of low energy density and safety hazards of existing supercapacitors are solved, and a superbattery capacitor with high energy density and safety is achieved.

CN119626786APending Publication Date: 2025-03-14QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721428.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The low energy density of existing supercapacitors and high lithium-embedded capacity of graphite active substances, resulting in the positive electrode requiring five times the weight to match the capacity, which increases production complexity and cost, and there are safety risks in the charging and discharging process of ternary positive electrode materials.

Method used

Lithium titanate/carbon composite materials are used as the negative electrode active substance, and single-crystalline and polycrystalline nickel-cobalt lithium manganese oxide and lithium iron manganese phosphate/carbon composite materials are used as the positive electrode active substances. By optimizing the particle size and weight ratio and combining with a high porosity separator, the energy density and safety of the battery are improved.

Benefits of technology

It improves the mass energy density and volume energy density of the battery, enhances the safety and service life of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626786A_ABST
    Figure CN119626786A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical energy storage, and particularly relates to a titanium-based super battery capacitor and a preparation method thereof. The titanium-based super battery capacitor comprises a shell, a positive plate, a negative plate, a diaphragm and electrolyte, the positive plate is composed of positive slurry and a positive current collector, the positive slurry is composed of a positive active material, a conductive agent and a binder, and the negative current collector is composed of a negative active material. The positive active material is a mixture of single-crystal nickel cobalt lithium manganate, polycrystal nickel cobalt lithium manganate and a lithium iron manganese phosphate / carbon composite material in a weight ratio of (20-30): (60-70): (5-15). The titanium-based super battery capacitor provided by the invention has the advantages of high mass energy density and volume energy density, good power performance and rate capability, excellent cycle performance, high safety and low manufacturing cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a titanium-based super battery capacitor and a preparation method thereof. Background Art

[0002] As the world attaches great importance to climate change and energy conservation and carbon reduction, the new energy industry has become one of the strategic emerging industries in the new century. As an important support and auxiliary technology for the new energy industry, the new energy storage material industry has attracted much attention from all parties. In my country, with the rapid development of pure electric vehicles and hybrid vehicles, the steady advancement of smart grids, the large-scale access of renewable energy such as wind and solar energy to the grid, and the growth of regional peak loads, various application problems have also emerged, which have put forward higher requirements on the energy density, power density and service life of electrochemical energy storage devices.

[0003] Supercapacitors have the characteristics of high power density and long cycle life. A typical example is a double-layer supercapacitor, whose positive and negative active materials are porous carbon. When charging, the high specific surface area of ​​the porous carbon is used to physically adsorb charges for energy storage. Its power density is ≥5kW / kg and its charge and discharge cycle life is 100,000 times, but its energy density is low (~5Wh / kg). The second is lithium-ion supercapacitors, whose positive active material is porous carbon and negative active material is graphite. When charging, the positive electrode stores electrical energy by physically adsorbing charges, and the negative electrode stores electrical energy by electrochemically inserting lithium. Its power density is ≥5kW / kg, and its charge and discharge cycle life is 50,000 times. The energy density has been improved to 15-20Wh / kg, but the energy density is still low. In addition, the lithium insertion capacity of graphite, the negative active material, is ~350mAh / g, which is much higher than the adsorption anion capacity of porous carbon, the positive active material, which is ~50mAh / g. Under the same weight, the negative electrode capacity is 5 times that of the positive electrode. Therefore, the positive electrode needs to be 5 times heavier than the negative electrode to achieve capacity matching, which brings great challenges to the electrode coating technology. In order to achieve positive and negative electrode capacity matching, previous technologies often pre-lithiate the negative active material graphite, which undoubtedly increases the complexity and cost of lithium-ion supercapacitor production.

[0004] Compared with graphite negative electrode materials, lithium titanate (Li4Ti5O 12 , abbreviated as LTO) is a zero-strain negative electrode material. The material will not deform during the insertion and extraction of lithium ions, and has good cycle performance; its charge and discharge voltage is stable, and the lithium insertion / extraction potential is 1.55V vs.Li / Li +(Specific capacity ~ 160mAh / g), it is not easy to produce lithium dendrites, and has good safety performance; it has a high lithium ion diffusion coefficient, can be charged and discharged at high rates, has good power performance and low-temperature charging and discharging capabilities, and can further improve the rate performance (large current charging and discharging capability, power density) by coating the surface of the material with a carbon layer with good conductivity. In terms of positive electrode materials, lithium nickel cobalt manganese oxide LiNi 1-x-y Co x Mn y Ternary cathode materials represented by O2 (0<x or y<1) have become a hot research and development spot in the field of electrochemical energy storage due to their high specific capacity (180~230mAh / g) and low cost advantages. Using lithium titanate / carbon composite materials as negative electrode active materials and lithium nickel cobalt manganese oxide as positive electrode active materials, the battery mass energy density and volume energy density can reach 90Wh / kg and 190Wh / L or more. However, there are certain safety hazards in the charging and discharging process of ternary cathode materials, and needle puncture is prone to fire. In addition, ternary materials are divided into single crystal and polycrystalline structures. Single crystal ternary materials have a stable structure and a long charge and discharge cycle life, but poor rate performance, while polycrystalline ternary materials are secondary particles formed by the agglomeration of primary particles. The charge and discharge structure stability and life are lower than those of single crystal ternary materials, but the rate performance is good. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a titanium-based super battery capacitor and a preparation method thereof.

[0006] To achieve the above purpose, the present invention adopts the following technical solution:

[0007] A titanium-based super battery capacitor comprises a shell, a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte. The positive electrode sheet is composed of a positive electrode slurry and a positive electrode current collector, wherein the positive electrode slurry is composed of a positive electrode active material, a conductive agent, and a binder. The positive electrode active material is a mixture of single-crystal lithium nickel cobalt manganese oxide, polycrystalline lithium nickel cobalt manganese oxide, and lithium iron manganese phosphate / carbon composite material in a weight ratio of 20-30:60-70:5-15.

[0008] The chemical formula of the single crystal lithium nickel cobalt manganese oxide and the polycrystalline lithium nickel cobalt manganese oxide is LiNi 1-x-y Co x Mn y O2 (0<x or y<1), the chemical formula of lithium iron manganese phosphate in lithium iron manganese phosphate / carbon composite material is LiMn x Fe 1-x PO4(0<x<1).

[0009] The particle size D50 of the single crystal lithium nickel cobalt manganese oxide is 2 to 5 μm, the particle size D50 of the polycrystalline lithium nickel cobalt manganese oxide is 5 to 15 μm, and the particle size D50 of the lithium iron manganese phosphate / carbon composite material is 0.5 to 3 μm.

[0010] The negative electrode sheet is composed of a negative electrode slurry and a negative electrode current collector, wherein the negative electrode slurry is composed of a negative electrode active material, a conductive agent, and a binder, and the negative electrode active material is a mixture of a lithium titanate / carbon composite material and porous carbon in a weight ratio of 85-95:5-15.

[0011] The specific capacity of the positive electrode active material per unit weight in the positive electrode sheet is 150-190 mAh / g; the specific capacity of the negative electrode active material per unit weight in the negative electrode sheet is 140-160 mAh / g; and the ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.1-1.5; the porosity of the diaphragm is 62%-75%.

[0012] The weight ratio of the positive electrode active material, the conductive agent and the binder is 90-97:1.5-5:1.5-5, and the weight ratio of the negative electrode active material, the conductive agent and the binder is 85-95:2.5-7.5:2.5-7.5.

[0013] The conductive agent in the positive electrode slurry and the negative electrode slurry may be the same or different and may be one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and graphitized carbon fibers;

[0014] The binders in the positive electrode slurry and the negative electrode slurry may be the same or different and may be one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene latex, and sodium carboxymethyl cellulose.

[0015] The diaphragm material is one of polypropylene, polyethylene and cellulose, and the thickness is 10-30 μm.

[0016] A method for preparing a titanium-based super battery capacitor comprises alternately stacking the negative electrode sheets and the positive electrode sheets, providing a diaphragm between two adjacent sheets, assembling a winding core, and placing the negative electrode sheets on both sides of the winding core; then vacuum drying the assembled winding core and placing it in a shell, injecting an electrolyte into the shell, and sealing the shell.

[0017] The positive electrode sheet is prepared by mixing the positive electrode active material with the conductive agent and the binder according to a weight ratio, adding a solvent to prepare a positive electrode slurry, and then coating the mixture on the positive electrode collector, drying, rolling, cutting, and vacuum baking to form a positive electrode sheet;

[0018] The negative electrode sheet is prepared by mixing the negative electrode active material with a conductive agent and a binder according to a weight ratio, adding a solvent to form a negative electrode slurry, then coating it on a negative electrode collector, and drying, rolling, cutting, and vacuum baking to form a negative electrode sheet.

[0019] More specifically:

[0020] (1) Preparation of positive electrode sheets: The positive electrode active material is mixed with the conductive agent and the binder according to the weight ratio, and a solvent is added to prepare the positive electrode slurry, which is then coated on the positive electrode collector. After drying, rolling, cutting and vacuum baking, the positive electrode sheets are made.

[0021] (2) Negative electrode sheet preparation: The negative electrode active material is mixed with the conductive agent and the binder according to the weight ratio, and a solvent is added to prepare the negative electrode slurry, which is then coated on the negative electrode collector. After drying, rolling, cutting and vacuum baking, the negative electrode sheet is made.

[0022] (3) Assembly: Stack the sheets in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet ... to form a winding core, and the outermost two sides of the winding core always remain negative electrode sheets.

[0023] (4) Liquid injection and sealing: After the core is vacuum dried, it is placed in a shell, and electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor.

[0024] The advantages and positive effects of the present invention are:

[0025] The positive electrode material of the present invention adopts single crystal lithium nickel cobalt manganese acid and polycrystalline lithium nickel cobalt manganese acid to combine, taking the advantages of the two as one, which can effectively improve the battery rate performance and cycle life; and further the system is compounded with lithium iron manganese phosphate with olivine structure, which can increase the structural support compared with the layered structure of the ternary positive electrode material, so it is not easy to collapse the structure during the charging and discharging process, has good stability, does not catch fire when punctured, has high safety and long service life; at the same time, due to the low cost of lithium iron manganese phosphate, the production cost can be reduced. Further, the particle size D50 of the single crystal lithium nickel cobalt manganese acid, polycrystalline lithium nickel cobalt manganese acid and lithium iron manganese phosphate of the present invention can be coordinated to increase the weight of the positive electrode active material per unit volume, thereby improving the mass energy density and volume energy density. In addition, adding optimized porous carbon with rich channels to the negative electrode slurry can effectively improve the rate performance of titanium-based super battery capacitors. In addition, by optimizing the weight ratio of single-crystal lithium nickel cobalt manganese oxide, polycrystalline lithium nickel cobalt manganese oxide and lithium iron manganese phosphate, the specific capacity of the positive active material is controlled at 150-180 mAh / g, the specific capacity of the negative active material is controlled at 140-160 mAh / g, and the ratio of the positive electrode sheet capacity to the negative electrode sheet capacity is coordinated to be 1.1-1.5. During tens of thousands of charge and discharge processes, the positive electrode is guaranteed to provide sufficient lithium ions, compensate for lithium ion loss, and improve the cycle life. Finally, a high-porosity diaphragm material is matched to adapt to the rate performance of the titanium-based super battery capacitor of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 SEM image of the positive electrode sheet of Example 1

[0027] Figure 2 Acupuncture test diagram of titanium-based super battery capacitor prepared in Example 1

[0028] Figure 3 Comparative Example 4: Needle puncture test diagram of titanium-based super battery capacitor prepared

[0029] Figure 4 Comparative Example 11 Titanium-based super battery capacitor needle puncture test diagram DETAILED DESCRIPTION

[0030] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0031] Example 1

[0032] Positive electrode production: single crystal LiNi with particle size D50 of 3.7μm 0.7 Co 0.1 Mn 0.2 O2 weight 25kg, particle size D50 9.8μm polycrystalline LiNi 0.7 Co 0.1 Mn 0.2 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, and then coats it on the positive electrode collector, and after drying, rolling, cutting, the size is 19.7cm×14.7cm, and vacuum baking, it is made into a positive electrode sheet. The unit weight capacity of the positive electrode active material on the positive electrode sheet is 165mAh / g, and the attached Figure 1 This is a scanning electron microscope image of the positive electrode slurry on the positive electrode current collector.

[0033] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0034] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0035] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0036] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a 1C rate current is 50.8Ah, the mass energy density is 96.5Wh / kg, the volume energy density is 206.4Wh / L, the power density at a 10C rate current is 5.8kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.8%, the capacity retention rate of 50,000 times of 10C charge and discharge is 85.7%, and there is no smoke or fire in the needle puncture test, as shown in the attached Figure 2 shown.

[0037] Example 2

[0038] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0039] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0040] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0041] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0042] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.5Ah, the mass energy density is 93.5Wh / kg, the volume energy density is 198.4Wh / L, the power density at a current rate of 10C is 5.6kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.5%, the capacity retention rate of 50,000 times of 10C charge and discharge is 86.8%, there is no smoke or fire in the needle puncture test, and the monthly self-discharge rate is 2%.

[0043] Example 3

[0044] Positive electrode production: single crystal LiNi with particle size D50 of 3.3μm 0.82 Co 0.12 Mn 0.06 O2 weight 25kg, particle size D50 12.7μm polycrystalline LiNi 0.83 Co 0.11 Mn 0.06 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4PO4 / carbon composite material weighs 10kg of positive electrode active material, and 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride are added to the solvent N-methyl-2-pyrrolidone and stirred to make positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0045] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0046] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0047] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0048] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 51.2Ah, the mass energy density is 110.5Wh / kg, the volume energy density is 210.6Wh / L, the power density at a current rate of 10C is 5.2kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.6%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 84.5%, and there is no smoke or fire in the needle puncture test.

[0049] Example 4

[0050] Positive electrode production: single crystal LiNi with particle size D50 of 3.2μm 0.915 Co 0.065 Mn 0.02 O2 weight 25kg, particle size D50 9.5μm polycrystalline LiNi0.9 Co 0.05 Mn 0.05 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 178mAh / g.

[0051] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0052] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0053] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0054] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 51.8Ah, the mass energy density is 110.5Wh / kg, the volume energy density is 210.6Wh / L, the power density at a current rate of 10C is 5.2kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.7%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 82.5%, and there is no smoke or fire in the needle puncture test.

[0055] Example 5

[0056] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.2μm LiMn 0.7 Fe 0.3 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The specific capacity per unit weight of the positive electrode active material on the positive electrode sheet is 158mAh / g.

[0057] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0058] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0059] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0060] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.2Ah, the mass energy density is 92.3Wh / kg, the volume energy density is 193.4Wh / L, the power density at a current rate of 10C is 5.6kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.7%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 84.3%, and there is no smoke or fire in the needle puncture test.

[0061] Example 6

[0062] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 40kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 50kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0063] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0064] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0065] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0066] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.5Ah, the mass energy density is 92.7Wh / kg, the volume energy density is 199.3Wh / L, the power density at a current rate of 10C is 5.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.2%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 88.9%, and there is no smoke or fire in the needle puncture test.

[0067] Example 7

[0068] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 20kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 70kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0069] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0070] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0071] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0072] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.6Ah, the mass energy density is 93.8Wh / kg, the volume energy density is 197.2Wh / L, the power density at a current rate of 10C is 6.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 97.8%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 82.4%, and there is no smoke or fire in the needle puncture test.

[0073] Example 8

[0074] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0075] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose binder, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.15.

[0076] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0077] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0078] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.5Ah, the mass energy density is 93.1Wh / kg, the volume energy density is 196.4Wh / L, the power density at a current rate of 10C is 5.5kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.2%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 81.3%, and there is no smoke or fire in the needle puncture test.

[0079] Example 9

[0080] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0081] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.5.

[0082] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0083] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0084] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 51.1Ah, the mass energy density is 92.3Wh / kg, the volume energy density is 191.4Wh / L, the power density at a current rate of 10C is 5.3kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.6%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 87.9%, and there is no smoke or fire in the needle puncture test.

[0085] Example 10

[0086] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0087] Negative electrode sheet preparation: Take 85kg of lithium titanate / carbon composite material, 8kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose binder, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 152mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0088] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0089] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0090] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.5Ah, the mass energy density is 93.2Wh / kg, the volume energy density is 197.1Wh / L, the power density at a current rate of 10C is 6.5kW / kg, the 10C discharge capacity / 1C discharge capacity is 97.1%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 87.3%, and there is no smoke or fire in the needle puncture test.

[0091] Embodiment 11

[0092] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0093] Negative electrode sheet preparation: Take 90kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose binder, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 157mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0094] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0095] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0096] Test results: It has been determined that the discharge capacity of the titanium-based superbattery capacitor at a current rate of 1C is 50.6Ah, the mass energy density is 91.6Wh / kg, the volume energy density is 195.1Wh / L, the power density at a current rate of 10C is 5.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 94.8%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 83.8%, and there is no smoke or fire in the needle puncture test.

[0097] Example 12

[0098] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0099] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0100] Assembly: A cellulose separator with a porosity of 60% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost sides of the winding core.

[0101] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0102] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.5Ah, the mass energy density is 93.6Wh / kg, the volume energy density is 198.7Wh / L, the power density at a current rate of 10C is 5.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.8%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 81.5%, and there is no smoke or fire in the needle puncture test.

[0103] Embodiment 13

[0104] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0105] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0106] Assembly: A cellulose separator with a porosity of 72% is used as the separator. The sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost sides of the winding core.

[0107] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0108] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.7Ah, the mass energy density is 93.6Wh / kg, the volume energy density is 199.5Wh / L, the power density at a current rate of 10C is 5.9kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.8%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 87.1%, and there is no smoke or fire in the needle puncture test.

[0109] Comparative Example 1

[0110] Positive electrode production: polycrystalline LiNi with a particle size D50 of 7.6 μm 0.6 Co 0.1 Mn 0.3 O2 weight 80kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0111] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0112] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0113] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0114] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.4Ah, the mass energy density is 93.2Wh / kg, the volume energy density is 192.4Wh / L, the power density at a current rate of 10C is 5.9kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.8%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 72.3%, and there is no smoke or fire in the needle puncture test.

[0115] This comparative example shows that when the single crystal ternary positive electrode material in the positive electrode active material is removed, the rate performance and power performance become better, but the cycle performance becomes worse.

[0116] Comparative Example 2

[0117] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 80kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride are added to the solvent N-methyl-2-pyrrolidone and stirred to make positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0118] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0119] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0120] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0121] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.5Ah, the mass energy density is 93.6Wh / kg, the volume energy density is 202.5Wh / L, the power density at a current rate of 10C is 4.5kW / kg, the 10C discharge capacity / 1C discharge capacity is 82.1%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 88.5%, and there is no smoke or fire in the needle puncture test.

[0122] This comparative example shows that when the polycrystalline ternary positive electrode material in the positive electrode active material is removed, the cycle becomes better, but the rate becomes worse.

[0123] Comparative Example 3

[0124] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4PO4 / carbon composite material weighs 2kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 168mAh / g.

[0125] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0126] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0127] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0128] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.6Ah, the mass energy density is 93.7Wh / kg, the volume energy density is 197.4Wh / L, the power density at a current rate of 10C is 5.5kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.3%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 74.1%, and the needle puncture test produced smoke but no fire.

[0129] This comparative example shows that when the weight ratio of lithium iron manganese phosphate in the titanium-based battery capacitor is reduced, the battery safety is reduced, smoke occurs during needle puncture, and the cycle performance deteriorates.

[0130] Comparative Example 4

[0131] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weighs 65kg, and 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride are added, and the solvent N-methyl-2-pyrrolidone is stirred and mixed to form a positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, and cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make a positive electrode sheet. The specific capacity per unit weight of the positive electrode active material on the positive electrode sheet is 168mAh / g.

[0132] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0133] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0134] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0135] Test results: It was determined that the discharge capacity of the titanium-based super battery capacitor at 1C rate current was 50.6Ah, the mass energy density was 93.7Wh / kg, the volume energy density was 197.4Wh / L, the power density at 10C rate current was 5.5kW / kg, the 10C discharge capacity / 1C discharge capacity was 96.3%, and the capacity retention rate of 50,000 times of 10C charge and discharge was 63.4%. After the needle puncture test, the battery caught fire and eventually pulverized. Figure 3 shown.

[0136] This comparative example shows that when the amount of lithium iron manganese phosphate added to the positive electrode slurry of the titanium-based battery capacitor is 0, the battery safety is further reduced, fire occurs during needle puncture, and the cycle performance is poor.

[0137] Comparative Example 5

[0138] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0139] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose binder, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 0.9.

[0140] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0141] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0142] Test results: It has been determined that the discharge capacity of the titanium-based superbattery capacitor at a current rate of 1C is 46.4Ah, the mass energy density is 75.5Wh / kg, the volume energy density is 165.4Wh / L, the power density at a current rate of 10C is 4.3kW / kg, the 10C discharge capacity / 1C discharge capacity is 81.6%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 60.1%, and there is no smoke or fire in the needle puncture test.

[0143] This comparative example shows that when the total capacity of the positive electrode is too low compared to the total capacity of the negative electrode, the positive electrode provides too few lithium ions, the discharge capacity is low, and the cycle performance is poor.

[0144] Comparative Example 6

[0145] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride are added to the solvent N-methyl-2-pyrrolidone and stirred to make positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0146] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose binder, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.7.

[0147] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0148] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0149] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 48.5Ah, the mass energy density is 97.6Wh / kg, the volume energy density is 209.5Wh / L, the power density at a current rate of 10C is 4.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 94.7%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 71.3%, and there is no smoke or fire in the needle puncture test.

[0150] This comparative example shows that when the total capacity of the positive electrode is too high compared to the total capacity of the negative electrode, the total capacity of the positive electrode is redundant, and too many lithium ions are consumed during charging, resulting in low discharge capacity and poor cycle performance.

[0151] Comparative Example 7

[0152] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0153] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0154] Assembly: A cellulose separator with a porosity of 40% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0155] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0156] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.4Ah, the mass energy density is 93.2Wh / kg, the volume energy density is 198.1Wh / L, the power density at a current rate of 10C is 3.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 78.5%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 73.5%, and there is no smoke or fire in the needle puncture test.

[0157] This comparative example shows that when the porosity of the diaphragm is too low, it is easy to block the shuttling of lithium ions during high-rate and high-current charging and discharging, resulting in low power density and poor rate performance and cycle performance.

[0158] Comparative Example 8

[0159] Positive electrode production: single crystal LiNi with particle size D50 of 3.9μm 0.6 Co 0.1 Mn 0.3 O2 weight 25kg, particle size D50 7.6μm polycrystalline LiNi 0.6 Co 0.1 Mn 0.3 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 160mAh / g.

[0160] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0161] Assembly: A cellulose separator with a porosity of 85% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0162] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0163] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 50.6Ah, the mass energy density is 93.6Wh / kg, the volume energy density is 198.5Wh / L, the power density at a current rate of 10C is 5.7kW / kg, the 10C discharge capacity / 1C discharge capacity is 96.6%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 83.1%, there is no smoke or fire in the needle puncture test, but the monthly self-discharge rate is 15%.

[0164] This comparative example shows that when the porosity of the diaphragm is too high, a micro short circuit occurs between the positive and negative electrodes, resulting in a high monthly self-discharge rate.

[0165] Comparative Example 9

[0166] Positive electrode production: single crystal LiNi with particle size D50 of 3.7μm 0.7 Co 0.1 Mn 0.2 O2 weight 25kg, particle size D50 9.8μm polycrystalline LiNi 0.7 Co 0.1 Mn 0.2 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 165mAh / g.

[0167] Negative electrode sheet preparation: Take 93kg of lithium titanate / carbon composite material, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose binder, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. At this time, the unit specific capacity of the negative electrode active material on the negative electrode sheet is 165mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0168] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0169] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0170] Test results: It has been determined that the discharge capacity of the titanium-based superbattery capacitor at a current rate of 1C is 50.9Ah, the mass energy density is 98.5Wh / kg, the volume energy density is 218.5Wh / L, the power density at a current rate of 10C is 4.3kW / kg, the 10C discharge capacity / 1C discharge capacity is 79.3%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 76.2%, and there is no smoke or fire in the needle puncture test.

[0171] This comparative example shows that when porous carbon is not added to the negative electrode, the unit specific capacity of the negative electrode active material on the negative electrode sheet is increased to 165 mAh / g. At this time, the pore structure in the negative electrode is reduced, and the diffusion rate of lithium ions is slowed down, resulting in poor power density and rate performance, and the cycle performance is also affected.

[0172] Comparative Example 10

[0173] Positive electrode production: single crystal LiNi with particle size D50 of 3.7μm 0.7 Co 0.1 Mn 0.2 O2 weight 25kg, particle size D50 9.8μm polycrystalline LiNi 0.7 Co 0.1 Mn 0.2 O2 weight 65kg, D50 1.1μm LiMn 0.6 Fe 0.4 PO4 / carbon composite material weighs 10kg of positive electrode active material, and takes 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride, adds solvent N-methyl-2-pyrrolidone, stirs and mixes, and adjusts into positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, cut into pieces with a size of 19.7cm×14.7cm, and vacuum baked to make positive electrode sheets. The unit weight specific capacity of the positive electrode active material on the positive electrode sheet is 165mAh / g.

[0174] Negative electrode sheet preparation: Take 80kg of lithium titanate / carbon composite material, 17kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 135mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0175] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0176] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0177] Test results: It has been determined that the discharge capacity of the titanium-based super battery capacitor at a current rate of 1C is 48.3Ah, the mass energy density is 79.1Wh / kg, the volume energy density is 181.4Wh / L, the power density at a current rate of 10C is 4.1kW / kg, the 10C discharge capacity / 1C discharge capacity is 90.1%, the capacity retention rate after 50,000 charge and discharge cycles at 10C is 79.8%, and there is no smoke or fire in the needle puncture test.

[0178] This comparative example shows that when an excessive amount of porous carbon is added to the negative electrode, the unit specific capacity of the negative electrode active material on the negative electrode sheet is increased to 135 mAh / g. Although porous carbon can increase the ion diffusion rate, due to the excessive amount added, the negative electrode needs to be coated with more and thicker slurry to meet the ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet of 1.4, which is counterproductive. It is difficult for lithium ions to diffuse into the interior of the electrode in a short time, resulting in a decrease in various battery performance indicators.

[0179] Comparative Example 11

[0180] Positive electrode production: single crystal LiNi with particle size D50 of 3.7μm 0.7 Co 0.1 Mn 0.2 O2 weight 25kg, particle size D50 9.8μm polycrystalline LiNi 0.7 Co0.1 Mn 0.2 O2 weighs 65kg, LiMn2O4 weighs 10kg with a D50 of 11.5μm, and 2.5kg of conductive carbon black, 1kg of carbon nanotubes, and 2.5kg of binder polyvinylidene fluoride are added to the solvent N-methyl-2-pyrrolidone and stirred to make a positive electrode slurry, which is then coated on the positive electrode collector, dried, rolled, and cut into pieces with a size of 19.7cm×14.7cm. After vacuum baking, a positive electrode sheet is made. The specific capacity per unit weight of the positive electrode active material on the positive electrode sheet is 165mAh / g.

[0181] Negative electrode sheet preparation: Take 88kg of lithium titanate / carbon composite material, 5kg of porous carbon, 3.5kg of conductive carbon black and 1kg of carbon nanotube conductive agent, 2.5kg of binder styrene butadiene latex and 1.5kg of sodium carboxymethyl cellulose, add solvent deionized water and stir to mix, adjust to negative electrode slurry, then apply it on the negative electrode collector, dry, roll and cut into pieces with a size of 20.1cm×15.1cm, and vacuum bake to make negative electrode sheets. The unit specific capacity of the negative electrode active material on the negative electrode sheet is 155mAh / g. The ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.4.

[0182] Assembly: A cellulose separator with a porosity of 70% is used as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, with the negative electrode sheets on the outermost two sides of the winding core.

[0183] Liquid injection and sealing: After vacuum drying, the core is placed in a shell, and the electrolyte is injected into the shell and sealed to obtain a titanium-based super battery capacitor. The electrolyte is 1.2 mol / L lithium hexafluorophosphate / propylene carbonate-dimethyl carbonate, ethyl methyl carbonate, vinylene carbonate, methylene disulfonate, p-toluenesulfonyl isocyanate (solvent weight ratio 20:40:40:1:0.75:0.25).

[0184] Test results: It was determined that the titanium-based super battery capacitor had a discharge capacity of 48.6Ah at a 1C rate current, a mass energy density of 84.7Wh / kg, a volume energy density of 176.4Wh / L, a power density of 3.8kW / kg at a 10C rate current, 85.6% of the 10C discharge capacity / 1C discharge capacity, and a capacity retention rate of 75.7% for 50,000 10C charge and discharge cycles. A puncture test resulted in a fire, as shown in the attached Figure 4 shown.

[0185] The above-mentioned embodiments only represent several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.

Claims

1. A titanium-based super battery capacitor, comprising a housing, a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte, characterized in that: The positive electrode sheet is composed of a positive electrode slurry and a positive electrode current collector, wherein the positive electrode slurry is composed of a positive electrode active material, a conductive agent, and a binder. The positive electrode active material is a mixture of single-crystal lithium nickel cobalt manganese oxide, polycrystalline lithium nickel cobalt manganese oxide, and lithium iron manganese phosphate / carbon composite material in a weight ratio of 20-30:60-70:5-15.

2. The titanium-based super battery capacitor according to claim 1, characterized in that: The chemical formula of the single crystal lithium nickel cobalt manganese oxide and the polycrystalline lithium nickel cobalt manganese oxide is LiNi 1-x-y Co x Mn y O2 (0<x or y<1), the chemical formula of lithium iron manganese phosphate in lithium iron manganese phosphate / carbon composite material is LiMn x Fe 1-x PO4(0<x<1).

3. The titanium-based super battery capacitor according to claim 2, characterized in that: The particle size D50 of the single crystal lithium nickel cobalt manganese oxide is 2 to 5 μm, the particle size D50 of the polycrystalline lithium nickel cobalt manganese oxide is 5 to 15 μm, and the particle size D50 of the lithium iron manganese phosphate / carbon composite material is 0.5 to 3 μm.

4. The titanium-based super battery capacitor according to claim 1, characterized in that: The negative electrode sheet is composed of a negative electrode slurry and a negative electrode current collector, wherein the negative electrode slurry is composed of a negative electrode active material, a conductive agent, and a binder, and the negative electrode active material is a mixture of a lithium titanate / carbon composite material and porous carbon in a weight ratio of 85-95:5-15.

5. The titanium-based super battery capacitor according to claim 1 or 4, characterized in that: The specific capacity of the positive electrode active material per unit weight in the positive electrode sheet is 150-190 mAh / g; the specific capacity of the negative electrode active material per unit weight in the negative electrode sheet is 140-160 mAh / g; and the ratio of the total capacity of the positive electrode sheet to the total capacity of the negative electrode sheet is 1.1-1.5; the porosity of the diaphragm is 62%-75%.

6. The titanium-based super battery capacitor according to claim 1 or 4, characterized in that: The weight ratio of the positive electrode active material, the conductive agent, and the binder is 90-97:1.5-5:1.5-5, and the weight ratio of the negative electrode active material, the conductive agent, and the binder is 85-95: 2.5~7.5:2.5~7.5。 7. The titanium-based super battery capacitor according to claim 6, characterized in that: The conductive agent in the positive electrode slurry and the negative electrode slurry may be the same or different and may be one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and graphitized carbon fibers; The binders in the positive electrode slurry and the negative electrode slurry may be the same or different and may be one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene latex, and sodium carboxymethyl cellulose.

8. The titanium-based super battery capacitor according to claim 1, characterized in that: The diaphragm material is one of polypropylene, polyethylene and cellulose, and the thickness is 10-30 μm.

9. A method for preparing a titanium-based super battery capacitor according to claim 1, characterized in that: The negative electrode sheets and the positive electrode sheets as described in claim 1 are alternately stacked, a separator is provided between two adjacent sheets, and a winding core is assembled, with the negative electrode sheets being provided on both sides of the winding core; the assembled winding core is then vacuum dried and placed in a shell, and an electrolyte is injected into the shell, and the shell is sealed.

10. The method for preparing a titanium-based super battery capacitor according to claim 9, characterized in that: The positive electrode sheet is prepared by mixing the positive electrode active material with the conductive agent and the binder according to a weight ratio, adding a solvent to prepare a positive electrode slurry, and then coating the mixture on the positive electrode collector, drying, rolling, cutting, and vacuum baking to form a positive electrode sheet; The negative electrode sheet is prepared by mixing the negative electrode active material with a conductive agent and a binder according to a weight ratio, adding a solvent to form a negative electrode slurry, then coating it on a negative electrode collector, and drying, rolling, cutting, and vacuum baking to form a negative electrode sheet.